Educational Theory and Its Relation to the Development of the Islamic Education Curriculum - Guna, Aryogo Adi; Fauzi, Muh; Zuher, Yan Fahmi; Ilmi, Darul (Ahlussunnah: Journal of Islamic Education, 2025)
This article discusses the relationship between educational theories and the development of the Islamic Education Curriculum in the context of educational reform and innovation in Indonesia. Education is viewed as a conscious and purposeful process to develop the full potential of students, while the curriculum serves as an instrument that bridges educational theory with learning practices in the field. This study uses a descriptive qualitative approach with a library research method sourced from various primary and secondary literature, such as the works of John Dewey, Ki Hajar Dewantara, Paulo Freire, Piaget, and Bruner. The results of the study show that educational theories, including behaviorism, cognitivism, constructivism, and humanism, have contributed significantly to the direction and strategy of Islamic Religious Education curriculum development. These theories help educators understand the characteristics of students, determine learning objectives, and design processes and evaluations oriented towards spiritual, intellectual, and moral development. Thus, the synergy between educational theory and curriculum is key to realizing Islamic Religious Education learning that is relevant, contextual, and adaptive to the challenges of the times.